2008
DOI: 10.1007/s12288-008-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilia in hodgkin lymphoma

Abstract: The incidence of eosinophilia in Hodgkin lymphoma is approximately 15%. Both peripheral and tissue eosinophilia have been noted in Hodgkin lymphoma. Eosinophils have important role in pathobiology of Hodgkin lymphoma. The mechanism of eosinophilia remains unknown though various mediators like IL-5 and GM-CSF have been implicated. We present a case who was diagnosed to have Hodgkin lymphoma and hypereosinophilia. Keywords Hypereosinophilia · Hodgkin lymphoma Case reportA 9-year-old child presented to our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Eosinophilia is present in 15% of HL at diagnosis. Only rarely HE criteria are also met [ 178 , 179 ]. Furthermore, eosinophilia can be a feature of other chronic lymphoid diseases as well as of acute lymphoblastic leukaemia [ 180 183 ], where it can associate with organ damage and affect prognosis.…”
Section: Eosinophils In Haematological Disorders and Cancermentioning
confidence: 99%
“…Eosinophilia is present in 15% of HL at diagnosis. Only rarely HE criteria are also met [ 178 , 179 ]. Furthermore, eosinophilia can be a feature of other chronic lymphoid diseases as well as of acute lymphoblastic leukaemia [ 180 183 ], where it can associate with organ damage and affect prognosis.…”
Section: Eosinophils In Haematological Disorders and Cancermentioning
confidence: 99%
“…The German Hodgkin Lymphoma study group further demonstrated that eosinophilia is of prognostic relevance in nodular sclerosis‐subtype Classical Hodgkin Lymphoma patients, whereas in patients with mixed cellularity‐subtype Hodgkin Lymphoma, the effect on survival was weaker . These observational findings suggest that the prognostic relevance of eosinophils in Hodgkin Lymphoma depends on the specific histological subtype, however, they are not able to offer an explanation for this finding .…”
Section: Summary and Discussion Of The Casementioning
confidence: 94%
“…Even though the presence of a prominent tissue eosinophilia represents a common histopathologic feature of Hodgkin Lymphoma, eosinophils have been mainly regarded as ‘innocent' bystanders recruited and activated during the cellular reaction typical of Hodgkin Lymphoma. Recent research, however, challenges this notion . Eosinophils may act as important elements in the pathology of Hodgkin Lymphoma by providing cellular ligands to the Tumor Necrosis Factor (TNF) superfamily receptors (CD40, CD30, CD95/Fas) expressed on the surface of both Hodgkin and Reed Sternberg cells.…”
Section: Summary and Discussion Of The Casementioning
confidence: 99%
“…Eosinophilia and HL association is estimated to be present in 15-38% of all lymphoma patients 4,6 . Its prognostic significance is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that reactive eosinophilia appears in lymphoid malignancies. Its frequency is estimated to be about 15% of all Hodgkin`s lymphoma (HL) patients 4 . Reactive eosinophilia is based on treating the underlying condition.…”
Section: Introductionmentioning
confidence: 99%